Algae biopolymer towards sustainable circular economy. (April 2021) - Devadas, Vishno Vardhan; Khoo, Kuan Shiong; Chia, Wen Yi; Chew, Kit Wayne; Munawaroh, Heli Siti Halimatul; Lam, Man-Kee; Lim, Jun-Wei; Ho, Yeek-Chia; Lee, Keat Teong; Show, Pau Loke
Highlights: Polyhydroxyalkanoates are biopolymers found in microalgae cell. Novel technologies with additives improve the biopolymer mechanical properties. Life cycle of biological composting have greenhouse gases credits. Carbon sequestration of 1 kg algae biomass assimilates 1.83 kg atmospheric CO2 . Algae cultivation in photobioreactor does not require arable land. Abstract: The accumulation of conventional petroleum-based polymers has increased exponentially over the years. Therefore, algae-based biopolymer has gained interest among researchers as one of the alternative approaches in achieving a sustainable circular economy around the world. The benefits of microalgae biopolymer over other feedstock is its autotrophic complex to reduce the greenhouse gases emission, rapid growing ability with flexibility in diverse environments and its ability to compost that gives greenhouse gas credits. In contrast, this review provides a comprehensive understanding of algae-based biopolymer in the evaluation of microalgae strains, bioplastic characterization and bioplastic blending technologies. The future prospects and challenges on the algae circular bioeconomy which includes the challenges faced in circular economy, issues regard to the scale-up and operating cost of microalgae cultivation and the life cycle assessment on algal-based biopolymer were highlighted. The aim of this review is to provide insights of algae-based biopolymer towards a sustainable circular bioeconomy.